Agaricus sect. Xanthodermatei (Agaricales) of West Bengal, India - Tarafder, Entaj; Dutta, Arun Kumar; Karunarathna, Samantha C.; He, Mao-Qiang; Tian, Fenghua; Acharya, Krishnendu (Phytotaxa, 2023)
Four species of Agaricus (Agaricaceae, Basidiomycota) belonging to the A. sect. Xanthodermatei of A. subg. Pseudochitonia, viz. Agaricus punjabensis, A. endoxanthus, A. melanocarpus, and A. xanthodermulus, are described from West Bengal, India, based on morphological and molecular sequences (nrDNA ITS and LSU rDNA) data. Comprehensive descriptions, field photographs of the specimens, and comparisons with morphologically similar and phylogenetically related taxa are provided. Among the four taxa, Agaricus punjabensis, A. melanocarpus, and A. xanthodermulus represent their first records for India, and Agaricus endoxanthus is newly reported for the state of West Bengal.